Geographies of Ageing: Social Processes and the Spatial Unevenness of Population Ageing - Davies, Amanda; James, Amity (Ashgate, 2011)
Population ageing is projected to affect all countries across the world in coming decades. The current rate of population ageing is unprecedented in human history with population projections indicating that this will be an enduring trend. Moreover, population ageing is spatially pervasive, affecting every man, woman and child. This has considerable implications for policy responding to the economic, social and healthcare outcomes of population ageing. The potential economic implications have been likened to those of the 2008 global financial crisis. This book examines the patterns and causes of uneven population ageing. It identifies those countries and localities most likely to experience population ageing and the reasons for this. Attention is also given to the role that youth migration, labour force migration, retirement migration and ageing in place have in influencing the spatial concentrations of older people. The book brings together a range of diverse international case studies to illustrate the importance of understanding the causes of population ageing. Case studies include a review of ageing in Florida's (USA) labour force, an investigation into the housing arrangements for the elderly in Northern Ireland and an assessment of the environmental stewardship activities of Grey Nomads on Western Australia's remote north coast.